The Incorporation of Philanthropy: Negotiating Tensions Between Capitalism and Altruism in Twentieth Century Canada - Liverant, Bettina (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
AbstractExploring the intersection points of institutionalized philanthropy and the Canadian corporation in periods of rising capital concentration, this paper demonstrates how changes in business approaches to charitable donation mirror larger transformations in corporate capitalism and organization, and the subsequent migration of these structures and mentalities to the charitable sector. In the first phase, at the turn of the last century, philanthropic practices came to be structured along corporate/professional models, with a new insistence that charities be well managed, fiscally responsible, and scientific in approach. In the postwar period, the expansion of corporate power was accompanied by the incorporation of philanthropic norms within capitalism. During this period, the logic of investment intensified and became increasingly explicit. Programs of donations were developed strategically for their potential to benefit business as well as the community. Corporate philanthropy evolved from a discretionary to an expected practice, offering visible testimony of business commitment to social responsibility.